KAJIAN DRPs (DRUG RELATED PROBLEMS) PENGGUNAAN ANTIBIOTIK PADA PASIEN DEMAM TIFOID ANAK DI INSTALASI RAWAT INAP DAN RAWAT JALAN RUMAH SAKIT X KOTA BANJARMASIN - Amalia Sholehah; Muhammad Zaini; Yuliana Salman (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2025)
Drug Related Problems (DRPs) are defined as events or conditions that possibly cause problems in treatment outcomes. so that it is necessary to study the occurrence of DRPs of antibiotic drugs in pediatric typhoid fever patients inpatients and outpatients at X Hospital, Banjarmasin City. This research is descriptive with a retrospective approach and uses a total sampling technique on 65 samples of medical records of pediatric patients aged 0-12 years. The results showed that patient characteristics were dominated by children aged 2-12 years (96.92%) and male gender (63.08%). The most common use of antibiotics was ceftriaxone (77.28%), followed by ampicillin, cefixime, azithromycin, and ciprofloxacin. In terms of DRPs incidence, 3 cases (4.61%) were found which were included in the category of choosing too high a dose, namely two cases in ampicillin and one case in ceftriaxone. The conclusion of this study is that the majority of aspects of antibiotic use are in accordance with guidelines and there are no DRPs problems because the doses given are in accordance with the usual dose tolerance limits.